2012
DOI: 10.1002/pds.3243
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of pharmacy and coded‐diagnosis information in identifying tuberculosis in patients with rheumatoid arthritis

Abstract: Purpose Previous studies suggest that disease-modifying anti-rheumatic drugs (DMARDs) increase tuberculosis (TB) risk. The accuracy of pharmacy and coded-diagnosis information to identify persons with TB is unclear. Methods Within a cohort of rheumatoid arthritis (RA) patients (2000–2005) enrolled in Tennessee Medicaid, we identified those with potential TB using ICD9-CM diagnosis codes and/or pharmacy claims. Using the Tennessee TB registry as the gold standard for identification of TB, we estimated the sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
0
15
1
Order By: Relevance
“…In a recently published study by Fiske et al () of RA Medicaid patients using a TB registry as the gold standard, ICD‐9 data alone grossly overestimated the number of TB cases (449 versus 10 confirmed cases in the registry); even when ICD‐9 codes were combined with pharmacy data, the false‐positive rate was still 75%. Trepka et al () also demonstrated that the sensitivity and PPV for discharge diagnosis for TB are low (47.7% and 38.3%, respectively).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…In a recently published study by Fiske et al () of RA Medicaid patients using a TB registry as the gold standard, ICD‐9 data alone grossly overestimated the number of TB cases (449 versus 10 confirmed cases in the registry); even when ICD‐9 codes were combined with pharmacy data, the false‐positive rate was still 75%. Trepka et al () also demonstrated that the sensitivity and PPV for discharge diagnosis for TB are low (47.7% and 38.3%, respectively).…”
Section: Resultsmentioning
confidence: 98%
“…Upon hand searching references, 1 additional study was identified. In total, 24 studies met our criteria for entry into the systematic review () (Figure and Table ). Seventeen studies examined bacterial infections, including 8 specifically examining the validation of pneumonia (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While there have been no specific reviews of ICD-9 code accuracy regarding FXS, SB, or MD in the United States, broader reviews of the literature reveal that unintentional coder errors caused by the limits of the clinician's knowledge and experience with the condition, misinterpreted information from the clinical record, and data entry mistakes lead to inaccuracy in ICD coding. [29][30][31] To control for miscoding, our inclusion criteria required two or more diagnoses of FXS, SB, or MD. The specification of at least two occurrences of a diagnosis was used in a Canadian study, which linked two surveillance systems; for spina bifida, they found an agreement rate of 64.1 %.…”
Section: Discussionmentioning
confidence: 99%